Analysis of cesarean section using Robson’s criteria in tertiary care center - Gurung, Padma; Malla, Sameer; Lama, Sushma; Pradhan Malla, Anagha; RC, Laxmi (Journal of Patan Academy of Health Sciences, 2022)
Introduction: This study aims to analyze all the women delivering in our institute according to the Robson’s classification. Robson’s ten group classification system (TGCS) endorsed by WHO, is a global standard tool for assessing, monitoring and comparing cesarean section rates at all levels. Method: This cross sectional study was conducted in the department of obstetrics and gynecology, Patan hospital, Patan academy of health sciences (PAHS), Lalitpur, Nepal over 12 months’ period. All women who delivered during this period were classified according to the Robson’s classification (TGCS) into a specific group. Relative size and overall cesarean section rate of each group were calculated. Result: A total of 4,985 cases were analyzed. The cesarean section rate was 57.7%. Group 1+2 represented nearly half (49%) of the obstetric population served during the study period. Group 2A was found to be the highest contributor (27.4%) followed by Group 5 (22.8%) and Group 1 (13.0%). In terms of indication for cesarean section -Fetal distress and previous cesarean section were found to be the most common indications. Similarly, nulliparous women were three to four times more likely to be delivered by cesarean section when labor was induced. Conclusion: From this study, we can conclude that for an effective reduction in the overall high cesarean section rate in our Institution, we need to focus on a more stringent protocol for inducing labor especially among nulliparous women and to practice evidence based guidelines. Redefining failed induction needs to be considered critically as well.